Pharmacological treatment with cabergoline in three cats with acromegaly - Soler Arias, Elber A.; García, Jorge D.; Castillo, Víctor A. (Revista Colombiana de Ciencias Pecuarias, 2017)
Anamnesis: Three cats diagnosed with diabetes mellitus (DM) were referred for examination due to the presence of insulin resistance signs, which included polyuria, polydipsia, polyphagia and high fructosamine levels, even with insulin glargine doses greater than 2 U/Kg/application. Clinical and laboratory findings: All patients had enlarged facial features along with increased interdental space. The biochemical tests revealed high IGF-1 concentrations. The magnetic resonance imaging displayed enlarged pituitary gland in one of the cats and images compatible with a pituitary macroadenoma in the other two. Acromegaly was the final diagnosis. Treatment approach: Oral cabergoline at 10 μg/Kg every 48 h was administered. Conclusion: The treatment with cabergoline successfully decreased IGF-1 concentrations and all insulin resistance signs, and it enhanced glycemic control for the DM in the three cats. Our results suggest cabergoline could be used for the treatment of acromegaly in cats.